Managing project risk delegate information : Monday 22 November 1999, One Great George Street Conference Centre, London (Thomas Telford, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 22 November 1999.
Keywords: Risk management -- Congresses.; Construction projects -- Congresses.; Construction industry -- Risk management -- Congresses.; elektronické knihy; electronic books